P299 Epidemiology of sexually transmitted infections at gabriel toure teaching hospital, bamako, mali. (14th July 2019) - Téguété, Ibrahima; Tounkara, Fatoumata Korika; Fane, Seydou; Sissoko, Abdoulaye; Traore, Youssouf
Abstract : Background: Sexually transmitted infections (STIs), including human immunodeficiency virus (HIV) remain a major public health problem in Africa. Indeed, they carried high morbidity and mortality in this region. The study aimed (1) to estimate the prevalence of STIs/genital infections in gynecological admissions at Gabriel Toure Teaching Hospital; (2) assess the association between HIV and STIs/genital infections. Methods: We carried out a cross-sectional study using a gynecological admissions database at Gabriel Toure Teaching Hospital, from January 1st, 2006 to December 31st, 2010. We estimated the prevalence of STIs and genital infections. A multivariate logistic regression model was used to estimate the Adjusted Odds Ratios (aOR) of HIV infection and risk factors with 95% Confidence Interval (95%CI). STIs and genital infections were the main exposure variables. Results: Among 9112 women admitted in a gynecological unit, 2240 women have laboratory test. Of these, STIs ( Chlamydia trachomatis and Trichomonas vaginalis ) prevalence were 7.8%, genital infection such as candida albicans (CA) represented 40.0%, bacterial vaginosis (G. vaginalis, U. urealiticum and M. hominis), 36.2%, while E. coli, Enterobacter and Enterococcus represented together 3.8%. STIs prevalence was higher in women aged 20 to 40 years old compared to adolescent (<20 years) and older women (>40), 6.0%% vs 1.9%, respectively. A same figure was observed with non-STIs. We noted a higher prevalence of STIs in cervicitis cases (11.8%). According to HIV status, CA was the main infection observed with a frequency of 60.0% in HIV+, 51.8% in HIV- and 36.3% in undetermined HIV status. The main risk factor associated with HIV infection was polygamous couple compared to monogamy (aOR = 4.87; 95%CI: 1.02 – 23.22). Conclusion: Women aged 20 to 40 years old carry the highest burden of genital infection at Gabriel Toure Teaching Hospital. CA was the most associated with HIV infection. Disclosure: No significant relationships.